ONLINE UNIVERSITY TEACHING SYSTEM, WITH 7 MODULES, QUANTIFIED WITH EXPERIENCE POINTS (XP), IN COMPUTER-ASSISTED TRAINING, PSYCHO-PEDAGOGICAL TRAINING MODULE - VĂIDĂHĂZAN, Remus; JULEAN, Iulia; MOHOLEA, Adina (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2022)
In the present study, a gamified didactic system structured on 7 modules was built. Each training module offered students mandatory and optional assignments. A number of 53 assignments were designed for this didactic system, distributed on the 7 modules, of which 23 assignments were mandatory and 30 were optional. Each assignment had an equivalent number of experience points (XP). For the correct solving of each assignment the student received the grade “admitted” and the equivalent XP. It was verified, by evaluating the implemented system, the general level of attractiveness and students’ perceptions on the level of pragmatism and on the hedonic aspect. Our research has shown that the degree of attractiveness of this system has been high enough to motivate us to implement it in the future. The stimulation and innovation that such a system brings are strong points that can promote involvement in didactic activity, but we must look for very effective ways to properly condition the solving of as many assignments as possible. Received 2022 July 12; Revised 2022 July 20; Accepted 2022 July 21; Available online 2022 June 30; Available print 2022 August 30. REZUMAT. Sistemul didactic universitar online, cu 7 module, cuantificat cu puncte de experiență (XP), la instruire asistată de calculator, modul de pregătire psihopedagogică. În studiul de față s-a construit un sistem didactic gamificat structurat pe 7 module. Fiecare modul de instruire a oferit studenților teme obligatorii și teme facultative. Au fost proiectate pentru acest sistem didactic un număr de 53 de teme didactice, distribuite pe cele 7 module, dintre care 23 de teme au fost obligatorii, iar 30 de teme au fost facultative. Fiecare temă a avut un număr echivalent de puncte de experiență (XP). Rezolvarea corectă a fiecărei teme aducea studentului calificativul “admis” și XP echivalent. S-a verificat, prin evaluarea sistemului implementat, nivelul general de atractivitate și percepțiile studenților asupra nivelului de pragmatism și asupra aspectului hedonic. Cercetarea noastră ne-a arătat că gradul de atractivitate al acestui sistem a fost suficient de mare astfel încât să ne motiveze pentru implementarea lui și în viitor. Stimularea și inovația pe care o aduc un astfel de sistem sunt puncte forte care pot promova implicarea în activitatea didactică, dar trebuie căutate modalități foarte eficiente care să condiționeze corect trimiterea unui număr cât mai mare de teme didactice. Cuvinte cheie: sistem didactic, puncte de experiență, instruire asistată de calculator, învățământ, online.